A Phase I Study of Tomotherapy in Patients With Primary Benign and Low-grade Brain Tumors: Late Toxicity and Quality of Life. (April 2016) - Boychak, Alex; Bauman, Glen; Fisher, Barbara; Abdulkarim, Bassam; Amanie, John; Fulton, Dorcas; Murtha, Albert; Patel, Samir; Urtasun, Raul; Ghosh, Sunita; Roa, Wilson H.
Abstract : Objectives: To evaluate longitudinal quality of life and late neurotoxicity (>12 mo) of tomotherapy in patients with primary benign and low-grade brain tumors. Methods: Between January 2006 and October 2009, 49 patients with brain tumors were treated with tomotherapy at 2 radiotherapy centers in Canada. The median age of the patients was 51.0 years (range, 21 to 74 y); there were 21 men (42.86%) and 28 women (57.14%). All 49 patients had an initial Karnofsky performance score ≥70. One patient (2.04%) received 45 Gy in 25 fractions, 27 patients (55.10%) received 50.4 Gy in 28 fractions, 15 patients (30.6%) received 54 Gy in 30 fractions, and 5 patients (10.2%) received 60 Gy in 30 fractions. A total of 47 patients were analyzed for late toxicity and outcomes. Results: Changes in the Karnofsky Performance Status of the patients did not reach statistical significance ( P >0.05). The majority of the quality of life parameters that reached a statistically significant level ( P <0.05) of change at 2 years were changes toward improvement (drowsiness, itchy skin, emotional functioning, fatigue, nausea, and appetite). Statistically significant ( P <0.05) interval deterioration in physical, role, and social functioning was observed. Actuarial overall survival at 5 years was 91.6%; disease-free survival at 5 years was 86.6%. Conclusions: IMRT helical tomotherapy is well tolerated, without statistically significant constitutional and late neurotoxicity up to the 2-year mark.